Organização da escuta musical: aspectos perceptivos e ferramentas analíticas - Eli Joory (2014)
The aim of this research was to create an investigative routine focused on listening to help achieve musical analysis process. For that, we looked for a theoretical framework that would deal with issues relating to the perception of the universe of sound; we looked into how the mind perceives sound surface and how the brain organizes the data perceived. We sought additional support in the theoretical body of Gestalt, which examines the perceptual principles of the visual universe. The objective is that the routine be used almost intuitively and have the power to allow the analysis of musical pieces from various periods and compositional techniques. We illustrated how to use the routine by analyzing pieces of different periods and compositional techniques: Claude Debussys La Cathédrale engloutie and Karlheinz Stockhausens Gesang der Jüngling.